Case Report: Effectiveness of Inetetamab combined with immunochemotherapy as first-line treatment in two cases of advanced gastric cancer with HER2 expression: a retrospective analysis - Wu, Shan; Zhang, Miao; Wang, Huaqing (Frontiers in Oncology, 2025)
This retrospective study analyzed the effectiveness of Inetetamab combined with an immunochemotherapy regimen as first-line treatment in two cases of advanced gastric cancer with human epidermal growth factor receptor 2 (HER2) expression. Both patients were elderly males diagnosed with gastric cancer presenting with distant metastasis at initial diagnosis. They were treated with a combination of Inetetamab, Tislelizumab, and the XELOX regimen (Inetetamab 300mg administered on Day 1; Tislelizumab 200mg administered on Day 1; Oxaliplatin 150mg administered on Day 2; Capecitabine 1.5g orally twice daily on Days 1-14; repeated every 3 weeks per cycle). Efficacy evaluation revealed that both patients achieved a partial response (PR). They attained progression-free survival (PFS) durations of 10 to 12 months. Treatment was well-tolerated through-out, with no occurrence of grade 3–4 adverse events. This therapeutic regimen provided significant survival benefits for these patients with advanced, multiply metastatic, HER2-positive gastric cancer. The findings of this study suggest a novel first-line treatment strategy for advanced gastric cancer, potentially improving treatment efficacy and quality of life for HER2-positive gastric cancer patients. Nevertheless, further clinical trials are warranted to validate the efficacy and safety of this treatment approach.